PENGARUH CTL DAN ASESMEN AUTENTIK TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SDN GUGUS SELATAN KEC. LENEK TAHUN AJARAN 2021/2022 - MUH THALAAT (COLLASE (Creative of Learning Students Elementary Education), 2022)
This study aims to determine the application of CTL and authentic assessment of science learning outcomes in fourth grade students of SDN  Gugus Selatan Kec. Lenek academic year 2021/2022. This type of research is a quasi experiment with the research design used is 2 x 2 factorial design. The study population amounted to 110 students. Of the 110 students, 60 students were selected as samples, drawn by random sampling technique. Data collection in this study using objective test method. Data were analyzed by one-way ANAVA test and two-way ANAVA followed by t-Scheffe test. The results of the research showed that: (1) there were differences in learning outcomes between students who followed the learning model of CTL and students following the conventional learning model, (2) there were differences in learning outcomes between students following the performance assessment and students following the project assessment 3) there is an interaction effect between the learning model and the assessment model used for the learning outcomes of the science, (4) there is a difference in the learning outcomes of the science in the students following the CTL learning model between the group of students following the performance assessment and the group of students following the project assessment. (5) there are differences in learning outcomes of IPA in students following the conventional learning model between groups of students following the performance assessment and group of students following the project assessment, (6) there are differences in the learning outcomes of the students on the performance assessment between the groups of students following the CTL learning model and groups of students following conventional learning model, (7) there is a difference in learning outcomes of IPA in students following project assessment between groups of students following a CTL learning model and a group of students following a conventional learning model.